The Role of Supplier Trust in Enabling the Twin Transition - Kokkinou, Alinda; van Elderen, Jan (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
The twin transition, the concurrent pursuit of digital and green transformation, requires organizations to develop specific dynamic capabilities. The present study examines how a Dutch textile company successfully transitioned from a linear to a circular business model. It identifies supplier trust as a critical yet underexplored enabler. Drawing on Dynamic Capability Theory and a longitudinal single-case study spanning 2021 to 2026, the study finds that trust-based supplier relationships underpin two key organizational dynamic capabilities: data analytic capability and sustainable supplier management capability. Supplier trust facilitates the cross-organizational data flows needed for evidence-based sustainability decision-making, while simultaneously enabling the collaborative R&D investments required for circular supply chain development. The findings challenge the assumption that the twin transition is primarily a technological challenge. Instead, the relational capabilities are foundational preconditions for effective digitalization.